PENGARUH KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA PEGAWAI PADA KANTOR SEKRETARIAT DPRD KABUPATEN MUNA - Farid Ismail Unsu; Nasrul Nasrul; Nursaban Rommy Suleman (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2021)
The purpose of this study were: 1). To know and identifies leadership influence on employee performance on the Parliament Secretariat Muna. 2) the effect of motivation on employee performance. 3) The effect of leadership and motivation on employee performance. The design of the study is a quantitative research. The population in this study were all employees of the Parliament Secretariat Muna totaling 39 people, using saturation sampling withdrawal. Retrieval of data in the form of interviews and questionnaires. The technique of data analysis using multiple regression models with SPSS 24. Research findings show that: 1) Leadership positive and significant effect on employee kineja. 2) Motivation positive and significant effect on employee kineja. 3) Kepempinan and motivation simultaneously positive and significant impact on employee kineja.